Some Unfinished Business in the Professionalization of the Personnel Man / Le spécialiste du personnel, un professionnel ? - Hall, Oswald (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 1961)
SummaryPersonnel men tend to define themselves as professionals. To find out whether they are justified in so doing, the Author describes the earmarks of a profession: specialization, spécific and unstandardized nature of the service to the client (who is more than just a customer), episodic and direct relationship between professional and client. With such criteria in hand, the Author argues that it is improbable that personnel work can be practised along the lines of a professional model; the bureaucratic model here appears more relevant.